Benign Convulsions with Mild Gastroenteritis - Young Ok Kim (Korean Child Neurology Society, 2020)
Benign convulsions with mild gastroenteritis (CwG) are a well-known type of benign seizures that occur in infants and children aged between 6 months and 3 years and are associated with acute (viral) gastroenteritis. The pathogens found in the stool of CwG patients are mostly rotavirus or norovirus, which can result in mild dehydration. Short-lasting seizures (≤ 5 minutes) occur in clusters within 24 hours, without provoking features such as fever, abnormal laboratory findings in the blood (e.g., hypoglycemia, hyponatremia, or hypocalcemia), or abnormal results in the cerebrospinal fluid (e.g., central nervous system infection). Electroencephalography in CwG patients shows normal or mildly abnormal findings, and brain imaging findings are normal. Affected children develop normally before and after the seizures. The occurrence of seizures does not require the repeated use of first- or second-line intravenous antiepileptic drugs in the acute stage or daily antiepileptic drug medications, since they usually do not recur and have a good prognosis. Patients with CwG rarely have a family history of epilepsy. Although the mean interval between enteric symptom onset and seizure onset in CwG is roughly 2 days, some patients can experience seizures before enteric symptoms, meaning that clinicians should exercise caution during early winter and spring, when the prevalence of CwG is especially high. Additionally, reports of CwG in Korea are roughly as common as in Japan and other East Asian countries, and pediatricians should therefore be familiar with its clinical characteristics and take care not to overprescribe antiepileptic drugs in patients with CwG.